Covalently linked multimers of gold nanoclusters Au102(p-MBA)44 and Au∼250(p-MBA)n. Issue 44 (21st September 2016) - Lahtinen, Tanja; Hulkko, Eero; Sokołowska, Karolina; Tero, Tiia-Riikka; Saarnio, Ville; Lindgren, Johan; Pettersson, Mika; Häkkinen, Hannu; Lehtovaara, Lauri
Abstract : Covalently-linked multimers of monodisperse gold nanoclusters Au102 ( p -MBA)44 and Au∼250 ( p -MBA) n were synthesized and plasmonic coupling was observed in Au∼250 ( p -MBA) n multimers. Abstract : We present the synthesis, separation, and characterization of covalently-bound multimers of para -mercaptobenzoic acid ( p -MBA) protected gold nanoclusters. The multimers were synthesized by performing a ligand-exchange reaction of a pre-characterized Au102 ( p -MBA)44 nanocluster with biphenyl-4, 4′-dithiol (BPDT). The reaction products were separated using gel electrophoresis yielding several distinct bands. The bands were analyzed by transmission electron microscopy (TEM) revealing monomer, dimer, and trimer fractions of the nanocluster. TEM analysis of dimers in combination with molecular dynamics simulations suggest that the nanoclusters are covalently bound via a disulfide bridge between BPDT molecules. The linking chemistry is not specific to Au102 ( p -MBA)44 . The same approach yields multimers also for a larger monodisperse p -MBA-protected cluster of approximately 250 gold atoms, Au∼250 ( p -MBA) n . While the Au102 ( p -MBA)44 is not plasmonic, the Au∼250 ( p -MBA) n nanocluster supports localized surface plasmon resonance (LSPR) at 530 nm. Multimers of the Au∼250 ( p -MBA) n exhibit additional transitions in their UV-vis spectrum at 630 nm and 810 nm, indicating the presence of hybridized LSPR modes. Well-defined structures and relatively small sizes make these systems excellent candidates for connecting ab initio theoretical studies and experimental quantum plasmonics. Moreover, our work opens new possibilities in the controlled synthesis of advanced monodisperse nanocluster superstructures.